Gerak Pemberdayaan Perempuan Pegiat UMKM melalui Proses Refleksi Diri di Gedangsewu, Pare, Kediri - Silviana, Ika; Husin, Mohamad (Asketik: Jurnal Agama dan Perubahan Sosial, 2019)
The fundamental problem of development is the equity of distribution to the smallest area. This homework is not only the responsibility of the village government, but it is also an obligation for people. To increase the development efforts, it needs to address the sustainability of awareness from various aspects and all parties. Especially for the rural citizen that have many limitations, a simpler pattern of development is needed to create vigorous empowerment and to increase the facility of access for the community. Through the self-reflection approach which are including the stages of sensory knowledge, the stage of reasoning, and the stage of the ratio of Gedangsewu UMKM, the local activists begin to build awareness. Based on the moral of development, all the steps above are the basis for managing the movement of empowerment. By using increasing awareness, local activists can be interpreted collective challenges, to create a common purpose and strengthen collective solidarity and identity. It is needed to maintain the politics of resistance because of the pragmatism and dependency lifestyle of the community in the recent system. Then it is necessary to create an independent mindset from the mind to the empowerment of implementation.